Hydrogeological characterisation of the impact of climate change and anthropogenic factors on groundwater resource in Klein Letaba River Catchment, Mopani District of Limpopo Province - Mohale, Masilo Gladness (My University, 2025)
Groundwater is the primary source of water supply for domestic use, agricultural and mining sectors in the Klein Letaba River catchment, which is located in the central-eastern part of the Limpopo Province. As a result of the arid-to-semi-arid nature of the climate, there is limited surface water in this catchment, which partly contributed to groundwater as the only dependable source of water supply for various uses. Periodic measurements of water level in several boreholes in this catchment indicated that there is a continuous drop in piezometric surface from time to time. This persistent problem necessitated a detailed hydrogeological characterisation of the Klein Letaba River catchment to understand the extent of the impacts of climate change and anthropogenic factors on groundwater resource. The main aim of the present study was to simulate groundwater flow, and evaluate the fluctuation of borehole water level in response to climate change and anthropogenic activities, thereby understand the extent of vulnerability of groundwater in the area. To achieve the aim, hydrogeological, geological, borehole logs, climate, soil, and digital elevation data, among many other spatial datasets were processed to determine aquifer parameters, MODFLOW layer groups, and develop boundary conditions. In addition, hydrochemical and environmental isotopes were used to trace the groundwater flow path, and to ascertain the inflows and outflow boundaries of the conceptual model of groundwater flow. The results show that groundwater recharge area occurs in the highly elevated south western sector, and it flows towards the low elevated north eastern part of the model boundary area. In addition, the tritium radiogenic isotope was employed to determine the mean residence time (MRT) of groundwater using the methods that were outlined in the previous studies. The results suggest that low tritium concentrations ranging from 0.2 to 1.9 TU correspond to the presence of old groundwater that resided in the aquifer for a prolonged period of time, probably prior to 1952 (<0.8 TU), while tritium values > 0.8 TU suggest the presence of a mixture of old and recently recharged water. MODFLOW NWT, along with its upstream weighted flow package (UPW), was used to carry out three-dimensional steady state modelling of groundwater flow, and assess the response of the groundwater level due to the impacts of climate change and anthropogenic factors. The results of the steady-state groundwater flow simulation indicated that recharge from the rainfall and river leakages are the most important components of the inflows that contribute to the availability of groundwater, accounting for 44% and 40%, respectively of the total inflows. The major outflow components include river leakage and evapotranspiration, which contribute 62% and 25%, respectively to the total discharge from the aquifer. These results show that groundwater and surface water interactions play an important role in the determination of the hydrological water balance. In that, the depletion of groundwater determines the fate of surface water and vice versa. The results of the zone budgets suggest that the weathered aquifer acts as a medium through which the fractured aquifer and the rivers are being replenished. The weathered aquifer supplies approximately 36% and 23% of the total outflow volume from its zone to the fractured aquifer and rivers, respectively. At the same time, the dam gains a minor fraction of water from the weathered aquifer owing to an insignificant fluctuation of the hydraulic head and the conductivity of the bottom of the dam. Recharge from the rain largely replenishes the fractured aquifer via the weathered aquifer, while the internal boundaries such as rivers and dam gain water from the two aquifers and surface runoff. The zone budget further indicates that both aquifers are hydraulically connected and water availability in both permeable layers depends on the amount of rainfall recharge, evapotranspiration, and groundwater abstraction. Thus, climate change and anthropogenic activities play a significant role in determining the availability of sustainable water supply in the area. Furthermore, the results signify the importance of the underlying fractured aquifer as the main source of water owing to its good hydraulic conductivity compared to the weathered aquifer. In summary, climate change and anthropogenic activities are the main drivers of the scarcity of water resource in the area.
Thesis (M.Sc. (Geology)) -- University of Limpopo, 2025
Keywords: Groundwater; Klein Lebata River; Water supply; Borehole Water; Hydrogeological; Climatic changes -- Effect of human beings on; Groundwater -- South Africa -- Limpopo; Letaba River Watershed (South Africa); Anthropogenic soils; Climatic changes -- South Africa -- Limpopo; Hydrogeological modeling